Studi Literatur Terkait Tantangan Biofisika Di Masa Depan Dalam Bidang Kedokteran Dan Teknologi Kesehatan - Rilla Ilma Ningrum; Muliyana Muliyana; Nazwa Adhelia Shabira; Siti Rahmania; Devina Rayzy Perwitasari Sutaji Putri (Program Studi Fisika, Jurusan Fisika, FMIPA, Universitas Mulawarman, 2026)
Biophysics is an interdisciplinary branch of science that integrates the principles of physics in studying biological systems, and has become an important foundation in the development of modern medical technology. Its applications cover a wide range of fields, from medical imaging, radiation therapy, biological systems modeling, to high-precision biomolecular technology. As the complexity of the global health system increases, the demands for efficiency, accuracy, and personalization of medical services are increasing. In this context, the role of biophysics is becoming increasingly important, while facing complex and multidimensional challenges. This literature study aims to identify and examine the main challenges faced by biophysics in its contribution to the future of medicine and health technology. Through a review of various recent scientific publications, it was found that these challenges include: the need for multi-scale biological data integration, both at the molecular, cellular, and organ levels, the development of theoretical models and physical simulations that are able to accurately represent the dynamics of biological systems, the limitations of real-time non-invasive diagnostic and treatment technologies, and ethical, safety, and regulatory issues in the implementation of biophysical technology in clinical practice.In addition, there are still gaps in cross-disciplinary collaboration, both between physicists, biologists, and medical personnel, as well as in educational contexts that do not fully support the integration of biophysics into the medical curriculum. This study concludes that collaborative and holistic strategic research, increasing scientific literacy in biophysics, and innovative regulatory and policy support are key to addressing these challenges and ensuring that biophysics can continue to be a driving force for innovation in future healthcare systems.